Influence of process parameters on mechanical performance and bonding area of AA2024/carbon-fiber-reinforced poly(phenylene sulfide) friction spot single lap joints. (15th October 2015) - Goushegir, S.M.; dos Santos, J.F.; Amancio-Filho, S.T.
Abstract : Graphical abstract: Highlights: AA2024-T3 and CF-PPS were successfully joined by friction spot joining technique. Rotational speed and joining time significantly influenced the bonding area. Bonding area was also greatly affected by joining pressure. Rotational speed showed the highest impact on the lap shear strength of the joints. Other parameters influencing shear strength were joining pressure and plunge depth. Abstract: The effects of friction spot joining process parameters on the bonding area and mechanical performance of single lap joints were investigated using full-factorial design of experiments and analysis of variance. On one hand, the main process parameters with significant influence on the bonding area were joining pressure, tool rotational speed and joining time. On the other hand, tool rotational speed and joining pressure displayed the highest influence on the lap shear strength of the joints followed by tool plunge depth, whereas the joining time was not statistically significant. The interaction between the rotational speed and joining time was the only interaction with a significant effect on the mechanical performance. Joints with ultimate lap shear forces varying between 1698 ± 92 N and 2310 ± 155 N were obtained. It was observed that generally a larger bonding area as a result of higher heat input leads to an increased mechanical performance of the joints. The generated regression model by the analysis of variance was used to identify an optimized set of parameters for increasing the lap shear strength of the joints to 2280 ± 88 N. Furthermore, the process temperature was monitored, which varied in the range of 370–474 °C.